Underground, Or Once There Was A Country - Harifa Ali Akbar Siregar (ULTIMART Jurnal Komunikasi Visual, 2015)
Film has the ability to bring memories. It is not only that, film is also capable of becoming a memory. Through uniqueness as audio and visual media, movies brings the audience out of confinement of space and time to get into a different situation. The example can be seen in the film by Emir Kustirica, Underground. The film that puts the power of memory, motion and movement, as well as the imagination. Underground not only invite the audience to know about a country, Yugoslavia, also brought them into the history and imagination which is sublime. Those which related with the state that once existed. Keywords: film, memory, movement, Emir Kusturica, Underground